Pelecehan Verbal terhadap Siswi Berjilbab: Bentuk, Faktor, dan Dampak Sosial - Rizki Julia; Neila Susanti (Jurnal Sosiologi Agama Indonesia)
Verbal sexual harassment against hijab-wearing female students in Deli Serdang, North Sumatra, has become a concerning issue, particularly due to its normalization within school environments. This study explores the forms of harassment experienced by the students, examines the factors driving such behaviors, and analyzes their psychological and social impacts. A phenomenological method was applied, involving in-depth interviews, participatory observations, and documentation. The results reveal that verbal harassment manifests in various forms, such as catcalling, inappropriate comments, and mockery of the hijab. Perpetrators often perceive these actions as harmless jokes, influenced by personal tendencies, peer pressure, and cultural norms rooted in patriarchy. Victims reported feeling fear, diminished confidence, and social withdrawal, but many remain silent due to stigma or lack of institutional support. Addressing this issue requires schools to provide safe reporting mechanisms, impose appropriate sanctions on perpetrators, and incorporate gender sensitivity education into their curricula. From a religious perspective, strengthening students’ awareness of moral and spiritual responsibilities, including gender equality, can further prevent harassment.